Analog Filters Using MATLAB - Wanhammar, Lars.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Analog Filters Using MATLAB provides a comprehensive overview of the theory and modern design methods for frequency-selective analog filters as well as describing how to select and design analog filters using MATLAB. The material covers the synthesis and design of classical passive filters with both lumped and distributed circuit elements, and active filters based on operational amplifiers, transconductors, and current conveyors. A supplementary toolbox in MATLAB is employed in order to minimize the need for advanced mathematics. The author includes many topics such as filter technologies, terminology, and basic concepts, common frequency-selective filters, and advanced approximations. Discussions of passive LC filters with lumped elements and passive filters with distributed elements are also included. Other topics covered are basic circuit elements and their descriptions, first- and second-order sections using single and multiple amplifiers, coupled forms and signal scaling, and various methods for immitance simulation among others. Analog Filters Using MATLAB can be used both at the undergraduate and graduate levels as well as for industrial designs. The author also includes a wealth of solved examples as well as end of chapter problems for both students and instructors.
to Analog Filters -- Synthesis of Analog Filters -- Passive Filters -- Filters with Distributed Elements -- Basic Circuit Elements -- First- and Second-Order Sections -- Coupled Forms -- Immitance Simulation -- Wave Active Filters -- Topological Simulation -- Tuning Techniques.
Keywords: Engineering; Complexity, Computational; Control engineering; Robotics; Mechatronics; Electrical engineering; Electronic circuits; Engineering; Circuits and Systems; Signal, Image and Speech Processing; Communications Engineering, Networks; Control, Robotics, Mechatronics; Complexity; Electronic books